Accelerated Development of the Dual Orexin Receptor Antagonist ACT‐541468: Integration of a Microtracer in a First‐in‐Human Study. Issue 5 (10th March 2018) - Muehlan, Clemens; Heuberger, Jules; Juif, Pierre‐Eric; Croft, Marie; van Gerven, Joop; Dingemanse, Jasper
Abstract : The orexin system regulates sleep and arousal and is targeted by ACT‐541468, a new dual orexin receptor antagonist (DORA). Healthy male subjects received a single oral dose of 5–200 mg to assess safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), mass balance, metabolism, and absolute bioavailability utilizing a 14 C‐labeled, orally and intravenously (i.v.) administered microtracer. The drug was safe and well tolerated; the PK profile was characterized by quick absorption and elimination, with median time to reach maximum concentration (tmax ) of 0.8–2.8 h and geometric mean terminal half‐life (t1/2 ) of 5.9–8.8 h. Clear dose‐related effects on the central nervous system were observed at ≥25 mg, indicating a suitable PK‐PD profile for a sleep‐promoting drug, allowing for rapid onset and duration of action limited to the intended use. This comprehensive first‐in‐human study created a wealth of data, while saving resources in drug development.